OPTIMALISASI SURVIVAL KIT BERBASIS KELUARGA DALAM MENINGKATKAN KESIAPSIAGAAN DAN RESILIENSI PASCA BENCANA : KESIAPSIAGAAN DAN RESILIENSI PASCA BENCANA - Tosi Rahmaddian; Annisa Wahyuni; Delsa Dezolla; Sevilla Ukhtil Huvaid; Novia Zulfa Hanum; Intan Kamala Aisyiah (LPPM ITB AAS Indonesia Surakarta, 2026)
Hydrometeorological disasters in West Sumatra have disrupted the fulfillment of basic community needs and contributed to low levels of preparedness in facing emergency situations. This community service activity aims to optimize the utilization of family-based survival kits to enhance preparedness and resilience among disaster-affected communities in Padang City and Padang Pariaman Regency. The method employed a participatory approach, including needs assessment, distribution of survival kits, education on their use, and simple monitoring. The survival kits provided consisted of flashlights, stoves and regulators, rice cookers, boots, evacuation ropes, raincoats, and tarpaulins. The results showed that the community was able to understand the functions and proper use of the survival kits and utilize them to meet basic needs during emergency conditions. In addition, there was an improvement in awareness and preparedness behavior at the family level. The program also contributed to increasing the sense of security and adaptive capacity of the community in facing disasters. Therefore, optimizing family-based survival kits can be considered an effective approach to strengthening preparedness and resilience among disaster-affected communities.